2021
DOI: 10.1016/j.celrep.2021.109540
|View full text |Cite
|
Sign up to set email alerts
|

Two secured FACT recruitment mechanisms are essential for heterochromatin maintenance

Abstract: FACT (facilitate chromatin transcription) is involved in heterochromatic silencing, but its mechanisms and function remain unclear. We reveal that the Spt16 recruitment mechanism operates in two distinct ways in heterochromatin. First, Pob3 mediates Spt16 recruitment onto the heterochromatin through its Spt16 dimerization and tandem PH domains. Without Pob3, Spt16 recruitment is partially reduced, exhibiting a silencing defect and impaired H2A/H2B organization. Second, heterochromatin protein 1 (HP1)/Swi6 medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 55 publications
(71 reference statements)
1
29
0
Order By: Relevance
“…This suggests that FACT protects heterochromatin from illegitimate transcription and likely transcription-induced histone turnover. A recent study revealed that FACT is recruited to heterochromatin via an interaction with the chromoshadow domain of Swi6 ( Takahata et al, 2021 ). It is thus tempting to speculate that this interaction keeps FACT in the vicinity of heterochromatin and together with other silencing factors creates a physical barrier for RNAPII and histone replacement, which would promote the H3K9me3 state.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that FACT protects heterochromatin from illegitimate transcription and likely transcription-induced histone turnover. A recent study revealed that FACT is recruited to heterochromatin via an interaction with the chromoshadow domain of Swi6 ( Takahata et al, 2021 ). It is thus tempting to speculate that this interaction keeps FACT in the vicinity of heterochromatin and together with other silencing factors creates a physical barrier for RNAPII and histone replacement, which would promote the H3K9me3 state.…”
Section: Discussionmentioning
confidence: 99%
“…ChIP analysis of Spt16 exhibited that the binding level of Spt16 to the heterochromatic region in the pob3∆ strain was decreased to half that of the wild type, suggesting the existence of a Pob3-independent recruitment mechanism of Spt16 onto heterochromatin. Genetic analysis also revealed that pob3∆swi6∆ double disruption exhibited an additive silencing defect compared with that shown in each of the pob3∆ and swi6∆ single mutant strains [115]. Therefore, we assumed that the recruitment of Spt16 onto heterochromatin is partially dependent on Swi6.…”
Section: Fact Dependent Heterochromatic Silencing In Fission Yeastmentioning
confidence: 87%
“…Genetic analysis and ChIP-qPCR showed that fission yeast strains lacking pob3 + (pob3∆) had comparable levels of histone H3K9 methylation and Swi6 localization in the heterochromatic region to those of the wild type strain, but with high levels of heterochromatic expression of ncRNAs. Phenotypic analysis of the pob3∆ strain indicated that heterochromatic silencing was defective in heterochromatin without significant loss of levels of histone H3K9 methylation and HP1/Swi6 binding [114,115]. ChIP analysis of Spt16 exhibited that the binding level of Spt16 to the heterochromatic region in the pob3∆ strain was decreased to half that of the wild type, suggesting the existence of a Pob3-independent recruitment mechanism of Spt16 onto heterochromatin.…”
Section: Fact Dependent Heterochromatic Silencing In Fission Yeastmentioning
confidence: 97%
“…FACT associates with Swi6 and this association requires the nuclear rim protein Amo1 and the RNA processing Rix1 complex (RIXC) complex. FACT, Amo1, and RIXC are all required for heterochromatin maintenance, but dispensable for heterochromatin establishment [79–82]. The tethering of heterochromatin to Amo1 at the nuclear periphery may create a specialized domain with a higher concentration of silencing proteins, which aids the recruitment of FACT to suppress histone turnover [80].…”
Section: Regulating Histone Turnover At Heterochromatin In Wild‐type ...mentioning
confidence: 99%